Understanding perspectives and barriers that affect fishers’ responses to bycatch reduction technologies - Suuronen, Petri (Oxford University Press (OUP), 2022)
Reducing the capture of non-target species and juvenile fishes through a variety of gear modifications and bycatch reduction devices are presumed to provide long-term biological and socioeconomic benefits and improve the reputation of fisheries. The adoption of these technologies by fisheries, however, has been low compared to research and development efforts. Research has focused on technical design and catch rate responses to these technological interventions with a limited focus on assessing fishers’ attitudes towards these technologies. This essay gives a personal reflection, based on an extensive collaboration with fishers, of the perspectives and barriers that may affect their responses. I also provide suggestions on how to genuinely engage fishers in the process that could lead to agreeable solutions. Above all, change should be approached from the perspective of those whose behavior one is seeking to influence, acknowledging the heterogeneity among fisheries and fishers. The essential element for the success is fishers’ motivation and readiness to the change. Fishers need a clear vision of what the changes mean for their livelihood and evidence that the technology to minimize bycatch performs sufficiently well in various conditions.
Keywords: attitudes; credibility; dialogue; incentives; motivation; participation; trust